2016
DOI: 10.1016/j.ypmed.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of commercial weight-loss programs on blood pressure and lipids: a systematic review

Abstract: Our objective was to compare the effect of commercial weight-loss programs on blood pressure and lipids to control/education or counseling among individuals with overweight/obesity. We conducted a systematic review by searching MEDLINE and Cochrane Database of Systematic Reviews from inception to November 2014 and references identified by the programs. We included randomized, controlled trials ≥12 weeks duration. Two reviewers extracted information on study design, interventions, and mean change in systolic bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
(42 reference statements)
2
9
0
2
Order By: Relevance
“…Similar to ours, a randomised study with 104 pre-diabetic drivers showed a slight decrease of weight and BMI in the SMS intervention group, with no mean change in WC, fasting glucose and lipids between groups, over time or in interaction effect between groups and time [ 30 ]. This is also similar to the findings of several diet recommendation trials when lipid outcomes did not differ after intervention in spite of a slight weight loss [ 33 ]. Most probably, the achieved relative weight loss is not sufficient to result in substantial lipid changes in premorbid subjects unlike insulin resistance.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to ours, a randomised study with 104 pre-diabetic drivers showed a slight decrease of weight and BMI in the SMS intervention group, with no mean change in WC, fasting glucose and lipids between groups, over time or in interaction effect between groups and time [ 30 ]. This is also similar to the findings of several diet recommendation trials when lipid outcomes did not differ after intervention in spite of a slight weight loss [ 33 ]. Most probably, the achieved relative weight loss is not sufficient to result in substantial lipid changes in premorbid subjects unlike insulin resistance.…”
Section: Discussionsupporting
confidence: 89%
“…To identify the RCTs of these 24 programs, we updated a 2005 systematic review and have previously published these results . In brief, we searched MEDLINE and the Cochrane Database of Systematic Reviews from inception to November 2014.…”
Section: Methodsmentioning
confidence: 99%
“…We determined the range of reported within‐group mean weight change among RCTs by program and time point. Similar to our previous studies , we did not perform meta‐analyses given the heterogeneous study populations, varying analysis types, and lack of variance estimates. We compared the magnitude of median weight change within the testimonials with the mean weight change reported from the RCTs of the 10 programs.…”
Section: Methodsmentioning
confidence: 99%
“…Programs vary in terms of meeting evidence-based recommendations, such as high-intensity counseling, prescription of a moderately reduced-calorie diet, increased physical activity, and behavior change strategies [5, 9], and therefore may vary in effectiveness at impacting both weight and cardiometabolic outcomes.…”
Section: Introductionmentioning
confidence: 99%